Singularity - Sleator, William (New York : E.P. Dutton, 1985)
Sixteen-year-old twins Harry and Barry stumble across a gateway to another universe, where a distortion in time and space causes a dramatic change in their competitive relationship.
Booklist.
Notable/Best Books (A.L.A.).
School Library Journal.
5.7
5.7
7-10.
Keywords: Science fiction; Twins -- Fiction; Science fiction; Twins -- Fiction